2016
DOI: 10.1016/j.jecp.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Time knowledge acquisition in children aged 6 to 11 years and its relationship with numerical skills

Abstract: Acquisition of time knowledge (TK; the correct representation and use of time units) is linked to the development of numerical abilities, but this relationship has not been investigated in children. The current study examined the acquisition of TK and its association with numerical skills. A total of 105 children aged 6 to 11 years were interviewed with our Time Knowledge Questionnaire (TKQ), developed for purposes of this study, and the Zareki-R, a battery for the evaluation of number processing and mental ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Each participant learned to read the time on an iPad Air 2 touchscreen using an app “Interactive Telling Time.” Considering the complexity of children’s time conceptions and the potential difficulty of teaching them to tell time (Burny et al, 2009, 2011, 2013; Labrell et al, 2016), only the hour times (e.g., 1:00, 9:00, 12:00, which we defined having minute hand on 12) and half-hour times (e.g., 1:30, 3:30, 6:30, which we defined having minute hand on 6) were presented in the format of a 12-h clock to reduce the difficulty of the learning material. Ante meridiem (a.m.) and post-meridiem (p.m.) were not differentiated.…”
Section: Methodsmentioning
confidence: 99%
“…Each participant learned to read the time on an iPad Air 2 touchscreen using an app “Interactive Telling Time.” Considering the complexity of children’s time conceptions and the potential difficulty of teaching them to tell time (Burny et al, 2009, 2011, 2013; Labrell et al, 2016), only the hour times (e.g., 1:00, 9:00, 12:00, which we defined having minute hand on 12) and half-hour times (e.g., 1:30, 3:30, 6:30, which we defined having minute hand on 6) were presented in the format of a 12-h clock to reduce the difficulty of the learning material. Ante meridiem (a.m.) and post-meridiem (p.m.) were not differentiated.…”
Section: Methodsmentioning
confidence: 99%
“…Using this technique, five-year-olds were able to make some discriminations in this way between familiar events of different durations, even though they showed poor knowledge of the durations of periods of time described using time words associated with the conventional clock and calendar system (seconds, minutes, hours, and days). Indeed, perhaps unsurprisingly, a proper grasp of the durations of periods of time corresponding to conventional time words seems to be closely linked to children's numerical skills, and continues to develop over middle childhood (Labrell et al, 2016).…”
Section: A Single Process or Multiple Ones?mentioning
confidence: 99%
“…Furthermore, other studies performed in normal populations found relationships between time processing and calculation skills (Skagerlund & Träff, ), as well as general mathematical intelligence (Kramer, Bressan, & Grassi, ). Finally, a recent study found a strong association in primary school children between conventional time knowledge, measured with a questionnaire, and numerical skills, such as number facts, number line estimation, and number comparisons (Labrell, Mikaeloff, Perdry, & Dellatolas, ). Together, these findings speak in favor of positive associations between mathematical abilities and the precision of time estimation and discrimination skills.…”
Section: Introductionmentioning
confidence: 99%